Voice of customers: Text analysis of hotel customer reviews (cleanliness, overall environment & value for money) - Chan, Nicholas Kin Whai; Lee, Angela Siew Hoong * (2017)
The rise of the Internet has caused many changes on our daily lives. Internet has drastically changed the way we live our life, the way we spend our holidays, how we communicate with each other daily, and how we purchase products. The growth of Internet amongst consumer has generated content on the Internet by sources such as social media, review website, blogs, product fan page and many more. This has lead on to a new way of planning a holiday or looking for a suitable hotel to stay. Hence, hotel reviews websites have become a popular platform for customers to share their experiences, reviews, and recommendations on hotels, which they have visited. In Malaysia, hotel industry has been one of the most important economic growths of the country. The primary goal of a hotel is to satisfy customers, to be able to provide a high quality of service, and provide customers with a memorable experience whilst staying at the hotel. The purpose of this study is to understand and identify the range of factors, which may contribute to the satisfaction of customers as well as through expectations. Data was collected from online review websites such as Trip Advisor. Text analytics are used to analyze the contents collected.